Analysis of Interpersonal Communication Styles on Social Media Platform X (A Netnographic Study of the MARAH-MARAH Community) - Astrid Hanna Asyifa; Evie Sophia; Fitri Annisa Rachmah; Saiful Hadi (Universitas Ibn Khaldun, 2025)
This study examines interpersonal communication styles within the MARAH-MARAH Community on social media platform X, which serves as a collective space for emotional expression. The subjects of this research are X users actively engaged in expressing anger, social criticism, and personal experiences, while the object of study is interpersonal communication style, analyzed through Norton’s (1978) framework consisting of dominant, dramatic, friendly, contentious, and relaxed styles. The research employs a qualitative approach using netnography, involving participatory observation, documentation of posts, replies, and screenshots, as well as content analysis to capture interaction patterns and the cultural meaning of online communication within the community. The findings indicate that the most prominent communication styles are dramatic, contentious, and friendly. Communication patterns are characterized by emotional expression, the use of humorous or harsh language, and visual symbols such as emojis. Factors influencing style selection include emotional intensity, group solidarity, and the contextual relevance of ongoing social issues. Harsh language is not always interpreted as aggression but often as a form of solidarity and catharsis. In conclusion, the interpersonal communication styles within the MARAH-MARAH Community construct a collective identity that functions as both a channel for catharsis and a potential source of conflict. The implications of this study contribute to the development of interpersonal communication theory in the digital era and offer practical recommendations for managing online communities to foster healthier and more constructive interactions.